(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper evaluates riparian buffer zone violations and examine its consequences on the building level building-level flood vulnerability along River Ngadda in Maiduguri, northeastern Nigeria. Geographic Information Systems (GIS) was used to integrate high-resolution satellite images and building footprint data in order to determine structures in the river channel. The channel was digitized on full tank level and subdivided into five sections (A-E) in which graduated buffer zones of 10m, 20m and 30m which corresponding to Nigerian planning setback requirements-were generated. Spatial overlay analysis was used to measure encroachment extent and density along the river corridor, while building vulnerability was classified using distance-based proximity and summarized through a Vulnerability Index (VI, a weighted index of proportional exposure to flood risk). Spatial autocorrelation was used to determine patterns of clustering on a segment basis. Findings indicate a large encroachment of 3,065 buildings in the 30m buffer, of which 716 were in the most vulnerable 0-10m area. The VI values were 1.73-1.90 which showed moderate to high flood risk, and central urban segments were most vulnerable. The spatial analysis revealed mostly negative autocorrelation indicating fragmented and not clustered vulnerability likely reflecting incoherent informal encroachment. Comparative analysis of distance-based vulnerability and building density showed complementary data, whereby single-proxy measures could be a poor fitting characterization of risk. The results indicate that the river could have been less effective in flood attenuation capacity due to weak setback enforcement which was worsened by the excessive solid waste disposal which diminished the conveyance of the channels. The management suggestions are based on spatially oriented intervention: phased relocation of highest-risk structures in central segments, prohibition of the emergence of new communities, clearing of channels and waste management plans, and institutional reinforcement. Preventive management is essential in peripheral segments and expansion needs to be stopped before weakness is diminished.